Arthritis in leukemia - Louthrenoo W. (2014)
ABSTRACT: The clinical features of 19 patients who had arthritis and leukemia were reviewed and compared with those without arthritis. There was leukemic arthritis (characterized by absence of other evident causes and response to chemotherapy) in 14, septic arthritis in 4, and hemarthrosis in 1. Among those with leukemic arthritis, there was acute leukemia in 11 and chronic leukemia in 3. The arthritis presented before, simultaneously with, and after the diagnosis of leukemia in 5, 4, and 5 cases, respectively. Acute symmetrical polyarthritis mimicking rheumatoid was the most common presentation. The knee, wrist, and ankle were most commonly involved. Adegree of pain, which was out of proportion to the degree of inflammation, could be seen occasionally. Synovial fluid blast cells were identified in 33% of cases. The leukemic arthritis responded well to chemotherapy. Septic arthritis was an initial presentation of leukemia in 2 patients. There was no significant difference in hematologic parameters or in mortality rate between those with and without arthritis. In conclusion, symmetric polyarthritis mimicking rheumatoid and septic arthritis could be an initial presentation of leukemic arthritis. One should have a high index of suspicion in patients with acute arthritis, especially if there is already anemia and pain is out of proportion to swelling.